FACTORS AFFECTING THE VALUE OF NON-FINANCIAL COMPANIES ON THE INDONESIA STOCK EXCHANGE - Aurellia Chrestella; Dewi Sari Wijoyo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to obtain empirical evidence about the effect of independent variables on firm value. This research uses independent variables of managerial ownership, institutional ownership, capital structure, profitability, company growth, company size, and investment decisions. This study uses a population of non-financial companies listed on the Indonesia Stock Exchange from the period 2015 to 2017. There are 83 non-financial companies selected as the final sample and the hypothesis tested using multiple regression analysis. The results contained in the study show the influence of profitability, company growth, and investment decisions on firm value, while managerial ownership, institutional ownership, capital structure, and firm size have no influence on firm value